The problem with two-event sequence learning by pigeons - Zentall, Thomas R.; Peng, Daniel N. (Animal cognition, 2024)
Bonobos appear to show little evidence of learning to make one response (R1) to an AB sequence and a different response (R2) to sequences BB, AA, and BA (Lind et al. PLoS ONE 18(9):e0290546, 2023), yet under different conditions, pigeons can learn this (Weisman et al. Exp Psychol Anim Behav Process 6(4):312, 1980). Aspects of the bonobo procedure may have contributed to this failure. Most important, no response was required in the presence of the stimuli to encourage attention to them. Furthermore, learning to make one response to the target sequence and another to the other sequences involves a bias that allows for better than chance responding. With the two-alternative forced-choice procedure used with the bonobos, the R1 response is correct for one sequence, whereas the R2 response is correct for three sequences. To correct for this, there are three times as many AB trials as each of the other sequences. However, this correction allows a bias to develop in which reinforcement often can be obtained by using only the last stimulus seen as the basis of choice (e.g., when the last stimulus is B respond R1 when the last stimulus is A respond R2). This solution yields reinforcement on five out of six, or 83%, of the trials. In the present experiment with pigeons, using this two-alternative forced choice procedure, most subjects tended to base their choice on the last-seen stimulus. This design allowed subjects to use a suboptimal but relatively effective choice strategy.